Think JBJS - Mohit Bhandari (Journal of Bone and Joint Surgery, 2025)
Antibiotic-loaded ceramic bone grafts (ACBGs) are widely assumed to provide extended local antimicrobial protection, maintaining concentrations above the minimum inhibitory concentration (MIC) for 28 to 42 days. However, this time frame is mainly based on in vitro elution assays with simplified washout models, and its relevance to in vivo performance is uncertain. This study compared the in vivo and in vitro release and behavior of gentamicin from 2 commercial ACBGs. Gentamicin-loaded hydroxyapatite/calcium sulfate (HA-CS) and calcium sulfate (CS) composites were investigated using a murine implantation model and in vitro elution assays. Gentamicin content in recovered depot material and elution media was quantified by liquid chromatography with tandem mass spectrometry. Model calculations evaluated how the assay design affects the estimated time above the MIC. Both ACBGs released >98% of gentamicin within 6 hours and >99% within 24 hours in vivo. In vitro assays likewise indicated early depot depletion, with concentration-time profiles beyond 48 hours driven by serial dilution rather than release. Model calculations suggested that the apparent prolonged antibiotic activity in previous in vitro assays was largely due to the assay design, not to sustained release, implying that freely administered antibiotics could produce similar profiles. Neither ACBG demonstrated measurable sustained release beyond an initial 24-hour burst phase. This may have important clinical implications, as expectations of prolonged local antimicrobial protection are not supported by the cumulative-release data showing rapid antibiotic depot depletion.